Escaping the Margins of Society: New Media and Youth Language Practices across the Rural Urban Divide in Kenya - Erastus , Fridah Kanana; Orwenjo, Daniel Ochieng; Gathigia, Margaret Nguru (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
In Kenya, among the youth, traditionally there were established language practice differences where youth in the rural areas would speak the domicile mother tongue while the urban youth re-designed their identity by creating and communicating in ‘Sheng’. This is no longer the case as the rural-urban language divide is linguistically flattening due to increased use of digital media, urbanization of rural spaces and globalization. This paper describes new digital media language trends among Kenyan urban youth and explains how globalization and digital media have become the unifying factor between rural and urban youth language practices. The paper contends that the narrowing of the urban-rural dichotomy in language use seems to have created semi-homogenous language practices among the youth in both rural and urban areas. This has been made possible by affordable internet which gives the rural youth access to urban culture and global trends. The paper also describes how urbanization of rural towns and rural-urban-urban-rural migration has created pathways that carry urban language practices to previously rural areas and created a form of African modernity and urbanity in these spaces.